Quality of life after bariatric surgery: comparison of four different surgical procedures - Elrefai, Mohamad; Diouf, Stefanie; Weiß, Christel; Kienle, Peter; Otto, Mirko (Bariatric surgical practice and patient care, 2017)
Objective: To identify predictors that may affect postoperative quality of life (QOL) after bariatric surgery.Methods: German speaking patients who underwent bariatric surgery between 2003 and 2010 were included. Out of the total of 132 patients fulfilling the inclusion criteria, 113 could be reached via phone interview (85.6%). Sixty-five patients underwent laparoscopic Roux-en-Y gastric bypass (LRYGB), 26 laparoscopic sleeve gastrectomy (LSG), 15 patients biliopancreatic diversion with duodenal switch (BPD/DS), and 7 patients laparoscopic gastric banding (LAGB). The German version of the bariatric QOL index questionnaire was used.Results: The study participants achieved a mean score of 51.2 ± 10.2 points, which is in normal range of healthy individuals. Patients operated at younger age had a better QOL than elderly patients. Men and women showed comparable postoperative QOL. Patients who had been already working before surgery or started to work postoperatively achieved more QOL score points than those who did not. LRYGB, LSG, LAGB, and BPD/DS all equally resulted in a good QOL after surgery (51 ± 11.3, 51.9 ± 7.1, 45.3 ± 9.6, 54 ± 9.7, p = 0.2).Conclusion: LRYGB, LSG, LAGB, and BPD/DS do not differ in terms of QOL 3.3 years after surgery. Young age and pre- and postoperative integration into work are positive predictors for good QOL after surgery. Postoperative QOL is significantly correlated to magnitude of weight loss after surgery (both percentage of total weight loss and percentage of excess weight loss).
Gesehen am 27.11.2018